Suspect Subjects: Queer Legal Futures in the US after Bostock - Borchert, Laura (American Culture Studies, 2025)
Despite formal equality gains such as LGBTQ workplace protections (Bostock v. Clayton County 2020), heteronormative cultural orders still permeate queer rights discourse. Laura Borchert engages with the cultural-legal construction of sexual minorities in the US and deconstructs naturalized assumptions about ›the Queer‹ in US law and culture by conducting interdisciplinary wide readings of legal texts. She makes a strong case for utilizing suspect classification to secure queer rights and offers the first distinctively cultural studies perspective on equal protection and sexual orientation by using a queer hermeneutics of law.